Effect of rainfall interception and resting period on the soil seed bank - Magandana, Thabo Patrick; Hassen, Abubeker; Tesfamariam, Eyob (Frontiers in Agronomy, 2024)
The ecosystems across the world are affected by diverse impacts of climate change. Climate change affect the soil seed bank as it is determined by the plants that are above the ground. This study investigated effects of rainfall interception and resting period on grasland soil seed bank.. Rainfall interception was employed as main plot treatment at four different levels namely: (15%, 30%, 60% and 0%) and the main plot treatments were each replicated five times using the rainout shelters arranged as main plot treatments in a split plot experimental design. The main plots are 49 m 2 (7 m x 7 m) in size and were covered by metal frame structures with v-shaped clear acrylic bands on top without ultraviolet filter and these plots were sub-divided into two sub-plots to determine the effect of resting periods (70 and 90 days). The soil samples were 8 cm in diameter and 20 cm in depth (1005 cm 3 ). We used seed emergence method rather than seed separation method to determine the soil seed bank due to very small size of some seeds for some species. The 60% rainfall interception resulted in significantly high forb densities at both resting periods. The forb densities decreased by 32 and 35% at 15 and 30% while they increased by 195% at 60% rainfall interception compared to 0% rainfall interception at 70 days resting period. Resting period significantly affected grass densities at 60% rainfall as the densities were higher at 70 than 90 days resting period. At 90 days resting period, grass densities were significantly higher at 0% rainfall interception that than the rest of the treatments while the grass densities were significantly lower at 60% rainfall interception. The 60% rainfall interception resulted in significantly (p<0.05) higher total densities (forbs and grass) in both resting periods. Total density increased by 2.9 and 143.48% at 15 and 60% rainfall interception respectively. Our results show that drought has a negative effect on grass soil seed bank while it improves the forbs soil seed bank. Furthermore, the resting period has no significant effects on soil seed bank in grasslands.